Journey to the Centre of the Earth - Verne, Jules; Illustrated by Chan, K. Y. (Hong Kong Oxford University Press, 1993)
This series of readers has been completely revised and updated, using a new syllabus and new word structure lists. Readability has been ensured by means of specially designed computer software. Words that are above a level but essential to the story are explained and reinforced within the text.
Include Illustrations
Keywords: Core of the Earth -- Science fiction -- Adventure stories